Controlling the Formation of Sodium/Black Phosphorus IntercalationCompounds Towards High Sodium Content. Issue 8 (31st March 2021) - Werbach, Katharina; Neiss, Christian; Müllner, Alexander; Abellán, Gonzalo; Setman, Daria; Lloret, Vicent; Wild, Stefan; Hauke, Frank; Pichler, Thomas; Hirsch, Andreas; Peterlik, Herwig
Abstract: The solid‐state synthesis of pure sodium‐black phosphorus intercalation compounds (Na‐BPICs) has been optimized in bulk for two stoichiometric ratios. Specifically, in‐situ X‐Ray diffraction (XRD) allowed the precise identification of the optimal temperature range for the formation of Na‐BPICs: 94 °C–96 °C. Moreover, as the undesired formation of Na3 P takes place at this very same range, we succeeded in introducing a new synthetic route based on a fast‐thermal ball milling implementation that results in the bulk production of BPIC without Na3 P in 9 out of 10 cases. Finally, by combining XRD, Raman spectroscopy, and DFT calculations we developed a new structural model for Na‐based BPICs showing an increase of BP's unit cell with Na atoms incorporated in every second layer. These results will pave the way for the large‐scale synthesis and application of pure BPICs, which are of great interest in fields such as optoelectronics or energy storage. Abstract : Bulk production : The formation of the sodium/black phosphorus intercalated (BPIC) phase via solid‐state reaction was followed in‐situ using X‐ray diffraction. Parameters of this reaction were used to introduce a synthesis procedure that uses ball milling at elevated temperatures and results in the formation of a mixed BPIC/black phosphorus phase without intermetallic phases.